2003
DOI: 10.1007/s00264-003-0507-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial and gender variations in adult hip morphology

Abstract: Pelvic X-rays of 99 adult patients (198 hips) were analysed in 58 men and 41 women to determine the morphology of the adult hip in Malawians. For each hip the centre edge angle of Wiberg, the acetabular angle of Sharp and the acetabular head index were measured. For each parameter, women were more dysplastic than men, and for the acetabular angle of Sharp there was a significant gender difference (p<0.05, t test). Our figures were compared to those of Fujii et al. who had measured the same parameters in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 2 publications
0
21
2
2
Order By: Relevance
“…We have found that most studies investigating this relationship have been based on urograms and colon radiographs, with little or no information on tube-to-film distance, pelvic orientation, magnification, or centering of the X-ray beam (Croft et al 1991, Lau et al 1995, Smith et al 1995, Lavy et al 2003. Furthermore, most OA case definitions used have either been Croft's classification based solely on male urograms, or the classification of Lawrence and Kellgren, which is notoriously problematic regarding reproducibility (Sun et al 1997).…”
Section: Discussionmentioning
confidence: 94%
“…We have found that most studies investigating this relationship have been based on urograms and colon radiographs, with little or no information on tube-to-film distance, pelvic orientation, magnification, or centering of the X-ray beam (Croft et al 1991, Lau et al 1995, Smith et al 1995, Lavy et al 2003. Furthermore, most OA case definitions used have either been Croft's classification based solely on male urograms, or the classification of Lawrence and Kellgren, which is notoriously problematic regarding reproducibility (Sun et al 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Geographical variations have been reported in hip OA and its relationship to mild dysplasia. Japanese,17 18 African,19 20 Turkish21 and Sami22 populations appear to have different prevalences of hip OA and acetabular dysplasia, and different associations than in Western Europeans. A caveat of many cross-sectional studies is that the measures of dysplasia are often undertaken on hips with established OA and could be secondary to OA and remodelling rather than being a pre-existing primary risk factor for its development.…”
Section: Introductionmentioning
confidence: 91%
“…Despite this prediction, however, only a limited number of studies have analysed the morphological characteristics of the primate acetabulum from an anthropological perspective (Schultz, 1969;MacLatchy and Bossert, 1996;Canillas et al, 2011;Hogervorst et al, 2011;Bonneau, 2013;Hammond et al, 2013a). Although some anthropology-focused authors have analysed and contributed to the research on the morphology and variability of the human acetabulum (Havelock, 1893;Erickson et al, 2000;Rissech et al, 2001;Mafart, 2005;Bonneau et al, 2012), most of the information available has been obtained from studies conducted for medical purposes (Bullough et al, 1973;Müller-Gerbl et al, 1993;Feugier et al, 1997;Witte et al, 1997;Thompson et al, 2000;Gupta et al, 2001;Varodompun et al, 2002;Lavy et al, 2003;Leunig et al, 2003;Zilber et al, 2004;Govsa et al, 2005;Sampson, 2005;Tallroth and Lepist€ o, 2006;Ganz et al, 2008;Vandenbussche et al, 2008;K€ ohnlein et al, 2009;Krebs et al, 2009;Pollard et al, 2010;Nakahara et al, 2011;Zeng et al, 2012). Other studies have examined load transfer across the hip bone and the hip joint (Eckstein et al, 1994;Dalstra and Huiskes, 1995;Lazennec et al, 1997;Witte et al, 1997) and the thickness and stress of the cartilage in humans (Kur...…”
Section: Introductionmentioning
confidence: 94%